A new modeling method to estimate the heat transfer characteristics of supercritical aviation kerosene RP-3 with pyrolysis. (5th March 2023) - Zhang, Yifeng; Cao, Yong; Feng, Yu; Xu, Shuai; Wang, Jingyi; Qin, Jiang
Highlights: A new method is proposed to establish a correlation model of heat transfer. Thermal properties and chemical heat absorption together influence heat transfer. This correlation can be applied in a wide range of cracking conversion (up to 80 %). The established correlation has an error range lower than 10 %. Abstract: The heat transfer mechanism of hydrocarbon fuels is important for designing cooling structures for hypersonic craft. This study investigated the supercritical heat transfer characteristics of aviation kerosene RP-3 with pyrolysis, and proposed a method for establishing a new empirical correlation to estimate the heat transfer characteristics. The results indicated that the thermal properties and chemical heat absorption affected the heat transfer of the fuel during pyrolysis. In addition, chemical heat absorption influenced the heat transfer characteristics of hydrocarbon fuels because of secondary reactions and the non-linear relationship between the chemical reaction rate and components and concentrations of reactants, as well as the temperature of the fluid. Based on the considerable errors between the numerical results and those results obtained from the existing empirical correlations, a new correlation model was developed and was used to predict the heat transfer of supercritical RP-3 fuel over a large range of conversions.